Prognostic Accuracy of Presepsis and Intrasepsis Characteristics for Prediction of Cardiovascular Events After a Sepsis Hospitalization - Walkey, Allan J.; Knox, Daniel B.; Myers, Laura C.; Thai, Khanh K.; Jacobs, Jason R.; Kipnis, Patricia; Desai, Manisha; Go, Alan S.; Lu, Yun; Brown, Samuel M.; Martinez, Adriana; Clancy, Heather; et al. (Journal of Political Economy, 2022)
Across two large healthcare systems, intrasepsis factors improved postsepsis cardiovascular risk prediction as compared with presepsis cardiovascular risk profiles. Further exploration of sepsis factors that contribute to postsepsis cardiovascular events is warranted for improved mechanistic and predictive models.